Analysis of the Influence of Service Quality on General Patient Satisfaction and Loyalty at Lanto Dg Pasewang Hospital, Jeneponto Regency - Amelia AP, A. Rizki; Samad, Anshari; Patimah, Sitti (International Journal Labs, 2025)
Based on an initial survey conducted by researchers, the number of general patient visits from the first semester of 2023 illustrates that general patient visits are experiencing a downward trend. most of the people who are domiciled in Jeneponto Regency still prefer to receive treatment and fulfill health services outside Jeneponto Regency compared to Lanto Dg. Pasewang Hospital. The purpose of this study is to analyze the influence of service quality on general patient satisfaction and loyalty at Lanto Dg. Pasewang Hospital, Jeneponto Regency. The type of research used is quantitative with a cross sectional study approach consisting of 72 samples with a sampling technique, namely simple random sampling. The results of the study found that there was an effect of responsiveness (?=0.006), assurance (?=0.002), tangible (?=0.000), and reliability (?=0.004) on patient satisfaction; there was no effect of empathy (?=0.123) on patient satisfaction; There was an effect of responsiveness (?=0.004), assurance (?=0.022), tangible (?=0.003) and reliability (?=0.000) on patient loyalty; There was no effect of empathy (?=0.239) on patient satisfaction. It is necessary to provide input in the suggestion box for every aspect of service quality that is still considered lacking so that it can be input material for Lanto Dg. Pasewang Hospital, Jeneponto Regency in increasing satisfaction and maintaining patient loyalty.